Lansoprazole – Induce Black Hairy Tongue- A Case Report - Eliz Aryal; M Rajbhandari; Sabina Bhattarai (Nepal Journal of Dermatology, Venereology & Leprology)
Lansoprazole induced black hairy tongue has been rarely reported. The purpose of this paper is to report a case of lansoprazole induce black hairy tongue and review the literature. A 75 year man from eastern part of Kathmandu presented with black hairy fine growth from tongue along with discomfort, burning and halitosis from oral cavity after taking lansoprazole for acute peptic disease(APD) from over the counter and after discontinuation of lansoprazole, black hairy tongue was resolving. Clinically and histopathologically: lansoprazole induced black hairy tongue was confirmed. Black hairy tongue is characterized by abnormal hypertrophy and elongation of filliform papillae. Lansoprazole is a proton-pump inhibitor (PPI) with a racemic 1:1 mixture of the enantiomers dexlansoprazole which inhibits the stomach’s production of gastric acids.